Preparation of Nitrogen and Sulfur Co‐doped and Interconnected Hierarchical Porous Biochar by Pyrolysis of Mantis Shrimp in CO2 Atmosphere for Symmetric Supercapacitors. Issue 19 (8th October 2021) - Ding, Yan; Huang, Shuqiong; Sun, Yangkai; Li, Yunchao; Zhu, Lingjun; Wang, Shurong
Abstract: A porous functional biochar (MSCs) rich in N and S heteroatom doping was prepared by pyrolyzing mantis shrimp shells as the biomass source of the typical processing seafood waste in CO2 atmosphere. The physical and chemical properties of carbon materials were adjusted by the control of the pyrolysis temperature. In this study, maximum specific surface area (SSA) and pore volume of 484.5 m 2  g −1 and 0.291 cm 3  g −1, respectively of the MSCs material were reached at 700 °C. Moreover, it was found in the characterization test that heteroatoms, such as N and S were successfully introduced into the carbon microstructure. MSC‐750 contains N of up to 9.46 % and 0.52 % of S. Although its SSA is only 431.6 m 2  g −1, the specific capacitance of the 6 M KOH symmetrical supercapacitor at 1 A g −1 reaches the maximum value of 144.2 F g −1 among all samples due to the pseudocapacitance generated by its high content of heteroatomic functional groups. Abstract : A strategy for preparing porous functional biochars (MSCs) rich in N and S heteroatoms for symmetric supercapacitors is presented. The method involves pyrolyzing mantis shrimp shells as a biomass source, obtained from typical seafood‐processing waste under CO2 atmosphere.